ANALISIS IMPOR BERAS INDONESIA DAN FAKTOR-FAKTOR YANG MEMPENGARUHINYA (Studi Kasus Tahun 1986-2003) - Purbayu Budi Santosa; Ondo Ilarinduan PS (Jurnal Dinamika Ekonomi & Bisnis, 2006)
AbstractAgricultural sector specially food crop consistently have come to principal focus and priority of run strategy during 1968-1993. One of efficacy which have been reached is self sufficiency rice in the early year 1984 After that, various changes like climate trouble, change of orientation development of economics, and various other change ha\>e resulted Indonesia again become rice importing country in the year 1986. Instability of Indonesia rice crop and production, causing Indonesia cannot fid/ill requirement will consume Indonesia society rice which always experience of the make-up of along with resident growth rate which progressively mount. Result of research indicate that variable produce rice, fuptah rate value to US dollar and import tariff have an effect on to Indonesia rice import, as for variable consume society rice not have an effect. Keywords :  Import Rice, rice consumption and production, tariff import rice